SAW-GIS Analysis: Economic Potential of Batik MSME’s in Surakarta - Maulida Sania Taufikkurrohmah; Evi Gravitiani; Tetuko Rawidyo Putro; Danur Condro (Universitas Negeri Semarang, 2026)
Surakarta is the national center of the batik industry; however, its growth has not been supported by comprehensive spatial-economic mapping, resulting in overly general development policies. This study analyzes the economic potential of batik MSMEs in Surakarta using the Simple Additive Weighting (SAW) method and Geographic Information Systems (GIS). Unlike descriptive approaches, this study introduces a quantitative framework to measure potential based on three related variables: distance (accessibility), product completeness (competitive advantage), and price (market equilibrium). The SAW method is applied to determine development priority rankings. The results indicate that 53.7% of MSMEs fall into the high-priority category, 37% into the medium-priority category, and 9.3% into the low-priority category. These findings suggest that batik development in Surakarta requires differentiated strategies based on regional typologies. This study contributes to the development of a visual database and decision-support tools for local governments to formulate appropriate location-based empowerment programs. The integration of SAW and GIS provides a robust economic-spatial perspective, ensuring that development policies account for both geographical and competitive factors simultaneously. This approach offers practical contributions to MSME digitalization and regional economic planning, particularly for traditional industries transitioning into a digital ecosystem.